The Application of Islamic Values Behind The Practice of Hospital Social Responsibility in RSI Sultan Agung Semarang - Muinudin, Muhammad; Shodiq, Muhammad Ja’far (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2025)
AbstractThe phenomenon of Corporate Social Responsibility (CSR) has been debated among business people. In hospitals, Corporate Social Responsibility is an ethical obligation that requires hospitals and other organizations to do something useful, in this case providing quality health services for patients and the community. Apart from this, hospitals with sharia certification are also encouraged to always pay attention to the concept of sharia, namely placing Islamic values in every activity, including in their social activities. This article aims to understand how to practice hospital social responsibility at RSI Sultan Agung Semarang. The research method used is ethnomethodology. Through 5 employees of RSI Sultan Agung Semarang as key informants, the researcher found that RSI Sultan Agung Semarang practices Hospital Social Responsibility (HSR) by: (1) Providing discounts on hospital fees; (2) Conducting social services; (3) Spiritual guidance; (4) Development of Tahfidz House; (5) Providing training and health seminars for students, companies and government; (6) Providing Takjil, Iftar and suhoor during the month of Ramadan to patients, delivery and waiting patients and mosque congregations; and (7) Providing assistance for the cost of examination and hospitalization to Alim, Ulama, Umara and leaders of Islamic boarding schools who need health services. The ways and forms of HSR practices carried out reflect that RSI Sultan Agung as a business entity is not only profit oriented, but still prioritizes humanitarian aspects (social oriented) and religious aspects (spiritual oriented). Keywords: Ethnomethodology, Hospital Social Responsibility, Spiritual Oriented AbstrakFenomena Tanggung Jawab Sosial Perusahaan (CSR) telah menjadi perdebatan di kalangan pelaku bisnis. Di rumah sakit, Tanggung Jawab Sosial Perusahaan merupakan kewajiban etis yang mengharuskan rumah sakit dan organisasi lain untuk melakukan sesuatu yang bermanfaat, dalam hal ini memberikan pelayanan kesehatan yang berkualitas bagi pasien dan masyarakat. Selain itu, rumah sakit dengan sertifikasi syariah juga didorong untuk selalu memperhatikan konsep syariah, yaitu menempatkan nilai-nilai Islam dalam setiap kegiatannya, termasuk dalam kegiatan sosialnya. Artikel ini bertujuan untuk memahami bagaimana praktik tanggung jawab sosial rumah sakit di RSI Sultan Agung Semarang. Metode penelitian yang digunakan adalah etnometodologi. Melalui 5 orang karyawan RSI Sultan Agung Semarang sebagai informan kunci, peneliti menemukan bahwa RSI Sultan Agung Semarang mempraktekkan Hospital Social Responsibility (HSR) dengan cara: (1) Memberikan potongan harga untuk biaya rumah sakit; (2) Mengadakan bakti sosial; (3) Bimbingan rohani; (4) Pengembangan Rumah Tahfidz; (5) Memberikan pelatihan dan seminar kesehatan untuk mahasiswa, perusahaan dan pemerintah; (6) Memberikan takjil, buka puasa dan sahur pada saat bulan ramadhan kepada pasien, pengantar dan penunggu pasien serta jamaah masjid; dan (7) Memberikan bantuan biaya pemeriksaan dan rawat inap kepada para Alim, Ulama, Umara dan pimpinan pondok pesantren yang membutuhkan pelayanan kesehatan. Cara dan bentuk praktik HSR yang dilakukan mencerminkan bahwa RSI Sultan Agung sebagai entitas bisnis tidak hanya berorientasi pada keuntungan semata, namun tetap mengedepankan aspek kemanusiaan (social oriented) dan aspek keagamaan (spiritual oriented). Keywords: Ethnomethodology, Hospital Social Responsibility, Spiritual Oriented